Crystal structure of dibromido-(1-methyl-1H-imidazole-κ1N)-(3-(3-methyl-1H-imidazol-3-ium-1-yl)propanoato-κ1O)zinc(II), C11H16Br2N4O2Zn - Liu Pengju; Wang Zongwei; Guo Libing; Tang Junming (Zeitschrift für Kristallographie - New Crystal Structures)
C11H16Br2N4O2Zn, monoclinic, Cc (no. 9), a = 15.534(7) Å, b = 7.956(4) Å, c = 14.589(7) Å, β = 119.094(8)°, V = 1575.5(13) Å3, Z = 4, Rgt(F) = 0.0296, wRref(F2) = 0.0703, T = 296 K.